Efficiency of removal of iron, manganese, ammonium and organic matter from groundwater - Albrektienė, Ramunė; Rimeika, Mindaugas (International Conference “Environmental Engineering”, 2017)
The acceptable concentrations in groundwater are usually in excess of iron, ammonium and manganese. These compounds are inefficiently removed by means of ordinary technologies of ammonium ions, iron and manganese compounds removal from groundwater (water aeration and filtration through granular filter fillings) where groundwater contains high concentrations of organic compounds. Increased concentrations of organic compounds in groundwater occur in well fields where exploited aquifers have contact with surface water wells and are supplemented with water from open water bodies. Such well field is located in the town of Nida (Lithuania). The norms permitted by Council directive 98/83/EC on the quality of water intended for human consumption are exceeded by iron, ammonium, manganese and organic compounds in this well field. The present study examines the efficiency of drinking water treatment technology of three-stage filtration with aeration and insertion of coagulant (polyaluminum chloride) where ammonium ions, iron, manganese and organic compounds are removed from groundwater in an integral manner. Three fillings were used for filtration: quartz sand, zeolite and quartz sand with oxidizing bacteria. The drinking water treatment technology examined removes ammonium ions, iron, manganese and organic compounds from groundwater in an integral manner until the requirements of the norms of directive 98/83/EC are achieved.
Keywords: groundwater; iron; manganese; ammonium; organic matter; filtration; coagulation